Coal mine separation layer grouting leakage blocking fly ash based composite slurry, preparation method and application
Patent Information
- Application Number
- CN202611149543.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-07-31
AI Technical Summary
[0006]现有浆料虽已部分采用粉煤灰、矿渣等工业固废,但仍有大量其他类型的工业废渣尚未被有效纳入离层注浆材料体系,固废资源化利用的空间尚未充分挖掘
(一)本发明通过镁渣与油页岩渣的特定比例复配,镁渣的掺入可显著提高浆料的屈服应力、表观粘度和触变性,从宏观流变学层面抑制粗颗粒沉降;油页岩渣的多孔结构通过物理锚固和毛细吸附在微观层面锁定颗粒。二者从宏观和微观两个尺度同时发挥作用,协同抑制离析分层,使浆料在长距离输送和静止状态下保持良好的均匀性。
Smart Images

Figure REF-OBJ-1785308120308-000002
Abstract
Description
Technical Field
[0001] This invention relates to the field of coal mine delamination grouting technology, specifically to fly ash-based composite grouting for coal mine delamination grouting and sealing, its preparation method, and its application. Background Technology
[0002] Overburden separation grouting is a crucial technical means to control surface subsidence during coal mining and ensure safe mining of coal resources under three types of pressure (buildings, water bodies, and railways). This technology involves injecting filling material into the separation space beneath the key overburden layer to form an artificial filling body that supports the overburden, thereby effectively controlling surface subsidence and protecting surface buildings and the ecological environment. With the widespread application of this technology, the filling material, as a core factor determining the cost and actual effectiveness of separation grouting, has become a key research focus in this field.
[0003] Currently, delamination grouting filling materials are mainly formulated from fly ash, slag, and cement. A grout system with fly ash as the main material, supplemented with slag powder and cement, is one of the most widely used solutions in current delamination grouting projects. Cement acts as a cementing material, providing early strength; slag powder acts as an auxiliary cementing material, filling the gap in strength growth during the middle stage; and fly ash contributes to later strength through its pozzolanic activity. The combination of these three materials achieves a step-like strength increase from early to late stages.
[0004] However, existing delamination grouting systems still have the following shortcomings in practical engineering applications: First, the density difference between coarse particles and fine mud in the grout is large, which makes it easy for segregation and stratification to occur during long-distance pumping and static processes. This not only affects the uniformity and consolidation strength of the filling body, but also easily blocks the grouting pipeline, seriously restricting the efficiency of grouting construction.
[0005] To ensure pumping over long distances, the slurry needs to have good fluidity. However, this usually means increasing the water content, and an increased water-cement ratio significantly reduces the compressive strength of the backfill material, leading to a prominent contradiction between fluidity and strength. To ensure fluidity, backfill materials made of pure gangue or gangue mixed with fly ash exhibit low early strength (3d, 7d) and late strength (28d), both below 1 MPa. Maintaining sufficient consolidation strength while ensuring good fluidity has long been a technical challenge that has remained unresolved in this field.
[0006] Although existing grouts have partially incorporated industrial solid wastes such as fly ash and slag, a large amount of other types of industrial waste residues have not yet been effectively incorporated into the delamination grouting material system, and the potential for the resource utilization of solid waste has not been fully explored.
[0007] Therefore, developing a new type of delamination grout that can simultaneously improve grout stability, alleviate the contradiction between fluidity and strength, and has a higher solid waste utilization rate has important engineering application value. Summary of the Invention
[0008] This invention aims to provide a fly ash-based composite slurry for coal mine delamination grouting and sealing, its preparation method, and its application. It is used to reduce segregation and stratification of the slurry, improve the consolidation strength while ensuring good slurry fluidity, alleviate the contradiction between fluidity and strength, further reduce material costs, and realize the synergistic resource utilization of various industrial solid wastes.
[0009] To solve the above technical problems, the specific solution adopted in this invention is as follows: a fly ash-based composite grout for sealing and plugging delamination in coal mines, composed of the following components in parts by weight: 40-60 parts fly ash; 15-25 parts of slag powder; 8-15 parts cement; Magnesium slag, 10–22.5 parts; 5-15 parts of oil shale residue; Water, with a water-to-solid ratio of 0.8 to 1.2; The mass ratio of magnesium slag to oil shale slag is 1.5:1 to 3:1.
[0010] Preferably, the magnesium slag is industrial waste residue produced by the Pidgeon process for magnesium smelting, and is ground to a specific surface area ≥350m². 2 / kg, which contains f-MgO; oil shale slag is a solid waste residue after dry distillation or combustion of oil shale, which has a porous structure and contains residual carbon, and is ground to a particle size ≤75μm.
[0011] Preferably, the mass ratio of magnesium slag to oil shale slag is 2:1.
[0012] Preferably, the fly ash is Class III or higher power plant fly ash, and the slag powder is granulated blast furnace slag powder with a specific surface area ≥ 400 m². 2 / kg, the cement is P.O42.5 ordinary Portland cement.
[0013] Preferably, the f-MgO content in the magnesium slag is 5% to 15%.
[0014] Preferably, the β-C2S content in magnesium slag is not less than 40%.
[0015] Preferably, the specific surface area of oil shale slag is ≥400m². 2 / kg, the pore size distribution of the porous structure is 0.1~10μm.
[0016] Preferably, the fixed carbon content in oil shale residue is 5% to 20%.
[0017] The preparation method of the above-mentioned fly ash-based composite grout for coal mine delamination grouting and sealing includes the following steps: Step 1: Grind the magnesium slag powder to a specific surface area ≥ 350 m². 2 / kg; Grind oil shale residue to a particle size ≤75μm; Step 2: Weigh out 40-60 parts of fly ash, 15-25 parts of slag powder, 8-15 parts of cement, 10-22.5 parts of magnesium slag, and 5-15 parts of oil shale slag according to the mass ratio, and put them into a dry powder mixer and stir for 8-15 minutes to obtain a uniform composite dry powder. Step 3: Add the composite dry powder obtained in Step 2 into the pulping machine, add water at a water-to-solid ratio of 0.8 to 1.2, stir for 5 to 10 minutes until the slurry is uniform and free of agglomerates, and the fly ash-based composite slurry is obtained.
[0018] The above-mentioned fly ash-based composite grout for coal mine delamination grouting and sealing is applied in the filling of coal mine overburden delamination grouting and sealing.
[0019] Compared with the prior art, the present invention has the following advantages: (i) This invention utilizes a specific ratio of magnesium slag and oil shale slag. The incorporation of magnesium slag significantly improves the yield stress, apparent viscosity, and thixotropy of the slurry, inhibiting coarse particle settling at the macroscopic rheological level. The porous structure of the oil shale slag locks the particles at the microscopic level through physical anchoring and capillary adsorption. Both work simultaneously at the macroscopic and microscopic scales to synergistically suppress segregation and stratification, ensuring good homogeneity of the slurry during long-distance transport and in static conditions.
[0020] (II) This invention effectively compensates for slurry solidification shrinkage through the synergistic effect of the micro-expansion effect of f-MgO in magnesium slag and the water-retaining and slow-release effect of residual carbon in oil shale slag; the carbonization activity of β-C2S in magnesium slag and the local carbon source provided by residual carbon in oil shale slag work synergistically to contribute additional strength without increasing water consumption; the Mg dissolved from magnesium slag... 2+ Si dissolved from oil shale slag 4+ / Al 3+ The reaction generates MSH gel, which forms a calcium-magnesium binary composite gel network with CSH gel, resulting in a denser and more stable microstructure. The combined effect of these multiple synergistic mechanisms enables the slurry of this invention to achieve higher consolidation strength while maintaining good flowability, effectively alleviating the contradiction between flowability and strength.
[0021] (III) This invention achieves full-time strength growth through a ternary stepped strength system of cement (early stage) + slag (mid stage) + fly ash (late stage), superimposed with the synergistic enhancement effect of magnesium slag-oil shale slag.
[0022] (iv) This invention uses industrial solid waste (magnesium slag, oil shale slag, fly ash, and slag) as the main raw materials, supplemented by a small amount of cement, to achieve the synergistic resource utilization of various industrial solid wastes, significantly reducing the cost of delamination grouting materials and meeting the requirements of green mine construction. Detailed Implementation
[0023] This invention provides a fly ash-based composite grout for sealing and plugging delamination in coal mines, comprising the following components in parts by weight: 40-60 parts fly ash, 15-25 parts slag powder, 8-15 parts cement, 10-22.5 parts magnesium slag, 5-15 parts oil shale slag, and water (water-to-solid ratio of 0.8-1.2). The mass ratio of magnesium slag to oil shale slag is 1.5:1 to 3:1.
[0024] The magnesium slag is an industrial waste residue produced by the Pidgeon process for magnesium smelting, which is ground to a specific surface area ≥350 m². 2 / kg, containing f-MgO, with an f-MgO content of 5%–15%, and β-C2S content of not less than 40%. The oil shale residue is a solid waste residue from the dry distillation or combustion of oil shale, possessing a porous structure and containing residual carbon (fixed carbon content of 5%–20%), ground to a particle size ≤75μm and a specific surface area ≥400m². 2 / kg, with a porous structure and a pore size distribution of 0.1–10 μm. The fly ash is Class III or higher power plant fly ash, and the slag powder is granulated blast furnace slag powder with a specific surface area ≥400 m². 2 / kg, the cement is P.O42.5 ordinary Portland cement.
[0025] The preparation method of the fly ash-based composite slurry includes the following steps: Step 1: Grind the magnesium slag powder to a specific surface area ≥ 350 m². 2 / kg; Grind oil shale residue to a particle size ≤75μm; Step 2: Weigh out 40-60 parts of fly ash, 15-25 parts of slag powder, 8-15 parts of cement, 10-22.5 parts of magnesium slag, and 5-15 parts of oil shale slag according to the mass ratio, and put them into a dry powder mixer and stir for 8-15 minutes to obtain a uniform composite dry powder. Step 3: Add the composite dry powder obtained in Step 2 into a pulping machine, add water at a water-to-solid ratio of 0.8 to 1.2, stir for 5 to 10 minutes until the slurry is uniform and free of agglomeration, and the fly ash-based composite slurry is obtained.
[0026] The technical solution of the present invention will be described below through multiple embodiments and comparative examples: Example 1
[0027] The composite slurry is prepared according to the following mass proportions: 50 parts fly ash, 20 parts slag powder, 12 parts cement, 12 parts magnesium slag, and 6 parts oil shale slag (magnesium slag: oil shale slag = 2:1), with a water-to-solid ratio of 1.0.
[0028] Preparation method: Magnesium slag powder is ground to a specific surface area of 380m². 2 / kg, oil shale slag is ground to a particle size ≤75μm; the components are dry mixed for 10 minutes according to the ratio; water is added at a water-to-solid ratio of 1.0 and stirred for 8 minutes to obtain the composite slurry.
[0029] The slurry obtained in this embodiment was tested and found to have an initial flowability of 235 mm, a 2-hour bleeding rate of 2.8%, a 3-day compressive strength of 1.6 MPa, and a 28-day compressive strength of 4.3 MPa.
[0030] Example 2
[0031] The composite slurry is prepared according to the following mass proportions: 40 parts fly ash, 25 parts slag powder, 15 parts cement, 10 parts magnesium slag, and 5 parts oil shale slag (magnesium slag: oil shale slag = 2:1), with a water-to-solid ratio of 0.8.
[0032] The preparation method is the same as in Example 1.
[0033] The slurry obtained in this embodiment was tested and found to have an initial flowability of 205 mm, a 2-hour bleeding rate of 2.2%, a 3-day compressive strength of 1.9 MPa, and a 28-day compressive strength of 4.8 MPa.
[0034] Example 3
[0035] The composite slurry is prepared according to the following mass proportions: 60 parts fly ash, 15 parts slag powder, 8 parts cement, 10 parts magnesium slag, and 6.66 parts oil shale slag (magnesium slag: oil shale slag ≈ 1.5:1), with a water-to-solid ratio of 1.2.
[0036] The preparation method is the same as in Example 1.
[0037] The slurry obtained in this embodiment was tested and found to have an initial flowability of 265 mm, a 2-hour bleeding rate of 3.2%, a 3-day compressive strength of 1.3 MPa, and a 28-day compressive strength of 3.8 MPa.
[0038] Example 4
[0039] The composite slurry is prepared according to the following mass proportions: 45 parts fly ash, 18 parts slag powder, 10 parts cement, 17 parts magnesium slag, and 10 parts oil shale slag (magnesium slag: oil shale slag = 1.7:1), with a water-to-solid ratio of 1.0.
[0040] The preparation method is the same as in Example 1.
[0041] The slurry obtained in this embodiment was tested and found to have an initial flowability of 228 mm, a 2-hour bleeding rate of 2.5%, a 3-day compressive strength of 1.7 MPa, and a 28-day compressive strength of 4.5 MPa.
[0042] Example 5
[0043] The composite slurry is prepared according to the following mass proportions: 50 parts fly ash, 20 parts slag powder, 10 parts cement, 15 parts magnesium slag, and 5 parts oil shale slag (magnesium slag: oil shale slag = 3:1), with a water-to-solid ratio of 1.0.
[0044] The preparation method is the same as in Example 1.
[0045] The slurry obtained in this embodiment was tested and found to have an initial flowability of 225 mm, a 2-hour bleeding rate of 2.6%, a 3-day compressive strength of 1.8 MPa, and a 28-day compressive strength of 4.6 MPa.
[0046] Example 6
[0047] The composite slurry is prepared according to the following mass proportions: 50 parts fly ash, 20 parts slag powder, 12 parts cement, 20 parts magnesium slag, and 10 parts oil shale slag (magnesium slag: oil shale slag = 2:1), with a water-to-solid ratio of 1.0.
[0048] The preparation method is the same as in Example 1.
[0049] The slurry obtained in this embodiment was tested and found to have an initial flowability of 222 mm, a 2-hour bleeding rate of 2.6%, a 3-day compressive strength of 1.6 MPa, and a 28-day compressive strength of 4.4 MPa.
[0050] Example 7:
[0051] The composite slurry is prepared according to the following mass proportions: 50 parts fly ash, 20 parts slag powder, 12 parts cement, 22.5 parts magnesium slag, and 15 parts oil shale slag (magnesium slag: oil shale slag = 1.5:1), with a water-to-solid ratio of 1.0.
[0052] The preparation method is the same as in Example 1.
[0053] The slurry obtained in this embodiment was tested and found to have an initial flowability of 248 mm, a 2-hour bleeding rate of 3.0%, a 3-day compressive strength of 1.4 MPa, and a 28-day compressive strength of 4.0 MPa.
[0054] Comparative Example 1 The composite slurry is prepared according to the following mass proportions: 50 parts fly ash, 20 parts slag powder, 12 parts cement, 10 parts magnesium slag, and 8 parts oil shale slag (magnesium slag: oil shale slag = 1.25:1), with a water-to-solid ratio of 1.0.
[0055] The preparation method is the same as in Example 1.
[0056] The slurry obtained in this comparative example was tested and found to have an initial flowability of 242 mm, a 2-hour bleeding rate of 4.1%, a 3-day compressive strength of 1.2 MPa, and a 28-day compressive strength of 3.2 MPa.
[0057] Comparative Example 2 The composite slurry is prepared according to the following mass proportions: 50 parts fly ash, 20 parts slag powder, 12 parts cement, 18 parts magnesium slag, and 5 parts oil shale slag (magnesium slag: oil shale slag = 3.6:1), with a water-to-solid ratio of 1.0.
[0058] The preparation method is the same as in Example 1.
[0059] The slurry obtained in this comparative example was tested and found to have an initial flowability of 196 mm, a 2-hour bleeding rate of 3.8%, a 3-day compressive strength of 1.7 MPa, and a 28-day compressive strength of 3.5 MPa.
[0060] Comparative Example 3 The composite slurry is prepared according to the following mass proportions: 50 parts fly ash, 20 parts slag powder, 12 parts cement, 18 parts magnesium slag (magnesium slag: oil shale slag = ∞), 0 parts oil shale slag, and a water-to-solid ratio of 1.0.
[0061] The preparation method is the same as in Example 1.
[0062] The slurry obtained in this comparative example was tested and found to have an initial flowability of 188 mm, a 2-hour bleeding rate of 4.8%, a 3-day compressive strength of 1.5 MPa, and a 28-day compressive strength of 3.6 MPa.
[0063] Comparative Example 4 The composite slurry is prepared according to the following mass proportions: 50 parts fly ash, 20 parts slag powder, 12 parts cement, 0 parts magnesium slag, 18 parts oil shale slag, and a water-to-solid ratio of 1.0.
[0064] The preparation method is the same as in Example 1.
[0065] The slurry obtained in this comparative example was tested to have an initial flowability of 252 mm, a 2-hour bleeding rate of 5.6%, a 3-day compressive strength of 0.8 MPa, and a 28-day compressive strength of 2.1 MPa.
[0066] Comparative Example 5 The composite slurry is prepared according to the following mass proportions: 50 parts fly ash, 20 parts slag powder, 12 parts cement, 16 parts magnesium slag, and 4 parts oil shale slag (magnesium slag: oil shale slag = 4:1), with a water-to-solid ratio of 1.0.
[0067] The preparation method is the same as in Example 1.
[0068] The slurry obtained in this comparative example was tested and found to have an initial flowability of 192 mm, a 2-hour bleeding rate of 4.5%, a 3-day compressive strength of 1.6 MPa, and a 28-day compressive strength of 3.4 MPa.
[0069] Comparative Example 6 The composite slurry is prepared according to the following mass proportions: 50 parts fly ash, 20 parts slag powder, 12 parts cement, 9 parts magnesium slag, and 9 parts oil shale slag (magnesium slag: oil shale slag = 1:1), with a water-to-solid ratio of 1.0.
[0070] The preparation method is the same as in Example 1.
[0071] The slurry obtained in this comparative example was tested and found to have an initial flowability of 248 mm, a 2-hour bleeding rate of 5.2%, a 3-day compressive strength of 0.9 MPa, and a 28-day compressive strength of 2.5 MPa.
[0072] Comparative Example 7 The composite slurry is prepared according to the following mass proportions: 45 parts fly ash, 18 parts slag powder, 12 parts cement, 25 parts magnesium slag, 0 parts oil shale slag, and a water-to-solid ratio of 1.0.
[0073] The preparation method is the same as in Example 1.
[0074] The slurry obtained in this comparative example was tested and found to have an initial flowability of 175 mm, a 2-hour bleeding rate of 5.3%, a 3-day compressive strength of 1.3 MPa, and a 28-day compressive strength of 2.8 MPa.
[0075] The test results of each embodiment and comparative example are summarized in Table 1 below: Table 1 Summary of test results for each embodiment and comparative example
[0076] 1. Effect of the mixing ratio of magnesium slag and oil shale slag on slurry properties As can be seen from Examples 1 to 5, when the mass ratio of magnesium slag to oil shale slag is in the range of 1.5:1 to 3:1, the slurry has excellent comprehensive performance: the 2-hour bleeding rate is ≤3.2% and the 28-day compressive strength is ≥3.8MPa.
[0077] When the ratio of magnesium slag to oil shale slag deviated from the above range (Comparative Examples 1, 2, 5, and 6), the overall performance of the slurry decreased significantly. In Comparative Example 1, with a magnesium slag:oil shale slag ratio of 1.25:1, the 2-hour bleeding rate increased to 4.1%, and the 28-day compressive strength decreased to 3.2 MPa. In Comparative Example 2, with a magnesium slag:oil shale slag ratio of 3.6:1, the initial fluidity decreased to 196 mm, and the 28-day compressive strength decreased to 3.5 MPa. Comparative Example 5 (4:1) had a 2-hour bleeding rate of 4.5% and a 28-day strength of 3.4 MPa, while Comparative Example 6 (1:1) had a 2-hour bleeding rate of 5.2% and a 28-day strength of only 2.5 MPa, both significantly inferior to Examples 1-5.
[0078] The differences in performance may be due to several factors. When the magnesium slag ratio is too low (magnesium slag: oil shale slag < 1.5:1), the insufficient magnesium slag content in the slurry fails to provide adequate yield stress and thixotropy to suppress coarse particle settling. Simultaneously, the alkaline environment provided by magnesium slag hydration is insufficient to fully activate the pozzolanic activity of the oil shale slag, leading to a decrease in both anti-segregation performance and strength. Conversely, when the magnesium slag ratio is too high (magnesium slag: oil shale slag > 3:1), the relatively insufficient oil shale slag content prevents the full utilization of its porous structure's physical anchoring effect and the water-retaining and slow-release effect of residual carbon. Furthermore, excessive magnesium slag increases the slurry's water demand and reduces its fluidity, which is detrimental to the slurry's uniformity and strength development. Only within the 1.5:1 to 3:1 range specified in this invention can the thixotropic thickening of magnesium slag and the porous anchoring of oil shale slag form an effective physical synergy, and the alkaline activation of magnesium slag and the pozzolanic reaction of oil shale slag form a sufficient chemical synergy, thereby achieving optimal overall performance.
[0079] 2. Comparison of the effects of using magnesium slag and oil shale slag alone. Comparative Example 3 (using only magnesium slag, 18 parts) had a 2-hour bleeding rate of 4.8% and a 28-day strength of 3.6 MPa; Comparative Example 4 (using only oil shale slag, 18 parts) had a 2-hour bleeding rate of 5.6% and a 28-day strength of only 2.1 MPa. Example 1 (12 parts magnesium slag + 6 parts oil shale slag, totaling 18 parts) had a 2-hour bleeding rate of 2.8% and a 28-day strength of 4.3 MPa.
[0080] The above comparison shows that, under the condition of the same total solid waste content (18 parts each), the slurry made by compounding magnesium slag and oil shale slag in a specific ratio (2:1) exhibits significantly better anti-segregation performance (2h bleeding rate decreased from 4.8% / 5.6% to 2.8%) and strength (28d strength increased from 3.6MPa / 2.1MPa to 4.3MPa) than either magnesium slag or oil shale slag alone. This indicates a clear synergistic effect between magnesium slag and oil shale slag, rather than a simple performance additive effect. When magnesium slag is used alone, it lacks the physical anchoring of the porous structure of oil shale slag and the water retention and slow release of residual carbon. When oil shale slag is used alone, it lacks the alkaline activation environment and thixotropic thickening effect provided by magnesium slag. After compounding, their respective functional shortcomings are complemented, macroscopic rheological regulation and microscopic particle locking form a synergy, and alkaline activation and pozzolanic reaction form a linkage, thereby achieving a synergistic effect.
[0081] 3. Effect of total magnesium slag content on slurry properties In Comparative Example 7, with a magnesium slag content of 25 parts, the initial fluidity of the slurry decreased to 175 mm, the 2-hour bleeding rate reached 5.3%, and the 28-day strength was only 2.8 MPa. This indicates that excessive magnesium slag can lead to a sharp decrease in slurry fluidity, an increase in bleeding rate, and a decrease in strength. This is because excessive magnesium slag increases the water demand of the slurry, making it impossible to fully wet all particles under the same water-to-solid ratio, resulting in uneven slurry and incomplete hydration. Therefore, it is necessary to control the magnesium slag content within the range of 10–20 parts.
[0082] Based on the test data from the above embodiments and comparative examples, the mechanism by which the compounding of magnesium slag and oil shale slag improves the slurry performance in this invention can be summarized as follows: I. Synergistic inhibition of segregation and stratification This invention uses a specific ratio of magnesium slag and oil shale slag to synergistically suppress segregation and stratification of the slurry from both physical and chemical perspectives.
[0083] Synergistic effects at the physical level: The incorporation of magnesium slag significantly improves the yield stress, apparent viscosity, and thixotropy of fresh slurry. With increasing magnesium slag content, the viscosity and yield stress of the filling slurry show a continuous increasing trend. The increase in yield stress directly increases the resistance that coarse particles need to overcome to settle, achieving thixotropic thickening and thus fundamentally inhibiting segregation from a macroscopic rheological perspective. Simultaneously, oil shale slag possesses a loose and porous structure. Porous particles mechanically interlock with the surrounding slurry, anchoring coarse particles within the slurry network. Furthermore, the porous structure adsorbs free water through capillary action, reducing the free water content in the slurry and increasing its consistency. The combination of macroscopic rheological regulation by magnesium slag and microscopic particle locking by oil shale slag achieves a synergistic effect of thixotropic thickening and porous anchoring, thereby forming a multi-scale anti-segregation network from macroscopic to microscopic levels.
[0084] Chemical synergy: Magnesium slag contains a large amount of CaO, which dissolves OH- upon adding water. - This creates an alkaline environment. Oil shale slag is rich in SiO2 and Al2O3. In the alkaline environment provided by magnesium slag, the active SiO2 and Al2O3 in the oil shale slag can react with Ca(OH)2 to generate CSH gel and CAH gel. These gel substances form a three-dimensional network structure in the slurry. They not only physically thicken the slurry but also bind suspended particles within the gel network through chemical bonding. The particle surface is coated with gel, and the particles are bridged by gel to form an overall network. Once the particles are encapsulated in this network, even if the slurry is in a static state, the particles are difficult to redistribute due to the constraint of the gel bonds, thus effectively inhibiting segregation.
[0085] The complementary relationship between physical and chemical synergy: Physical thickening primarily inhibits the settling of coarse particles, while chemical cementation forms a multi-scale particle network. This network structure directly constrains coarse particles and provides overall constraint on medium and fine particles through the cementing effect of the gel. The thixotropic thickening of magnesium slag increases the resistance to particle movement at the macroscopic level, while the gel generated from the reaction of oil shale slag volcanic ash forms a chemically bonded particle network at the microscopic level. Both thickening and chemical cementation work simultaneously at both the macroscopic and microscopic scales, upgrading from single physical thickening to a dual guarantee of synergistic physical thickening and chemical cementation, ensuring good homogeneity of the slurry during long-distance transport and in static states.
[0086] II. Coordinated efforts to alleviate the contradiction between liquidity and strength This invention leverages the interaction between magnesium slag and non-mainstream components in oil shale slag to add weight to the strength side from three levels, thereby creating greater operational flexibility for fluidity.
[0087] (1) Synergistic effect of micro-expansion of f-MgO and water retention and slow release of residual carbon: f-MgO (free magnesium oxide) in magnesium slag hydrates to generate Mg(OH)2, and the reaction is slow but continuous. The volume expansion generated by MgO hydration can effectively compensate for the deformation of concrete caused by shrinkage and greatly reduce the generation of cracks. This reaction requires water, and the residual carbon in oil shale slag has a porous structure, which absorbs some free water in the early stage of mixing and slowly releases it in the subsequent hydration process. The water retention and slow release effect of residual carbon in oil shale slag provides timed water supply for the later hydration of f-MgO, so that the expansive hydration reaction of f-MgO can be fully carried out. In the closed space of delamination grouting, this micro-expansion effect can effectively compensate for the shrinkage during the solidification process of the grout and increase the density of the filling body. This invention transforms the harmful expansibility of magnesium slag f-MgO into a beneficial micro-expansion compensation effect, achieving a positive technical effect from a negative result.
[0088] (2) Synergistic effect of β-C2S carbonization activity and residual carbon as a carbon source: β-C2S in magnesium slag has both hydration and carbonization activity. Magnesium slag-based solid waste backfill material can be prepared through carbonization curing, and can absorb up to 16.34% CO2. The carbonized backfill material has high strength characteristics. The residual carbon in oil shale slag can provide a local carbon source inside the slurry, promoting the carbonization reaction of β-C2S in magnesium slag to generate CaCO3. This carbonization reaction does not consume water, but contributes extra strength, achieving strength improvement without increasing water consumption.
[0089] (3) Mg 2+ With Si 4+ / Al 3+ Composite gel network: Mg dissolved from magnesium slag 2+ Si dissolved from oil shale slag 4+ / Al3+ In an alkaline environment, it can react to form magnesium silicate hydrate (MSH) gel. The MSH gel and CSH gel coexist and complement each other, forming a calcium-magnesium binary composite gel network. The composite gel network is denser and more stable than the single CSH network, contributing higher strength at the same water-to-solid ratio.
[0090] The combined effect of the above three mechanisms enables the slurry of this invention to achieve additional strength without increasing the water content. This increase can be used to offset the strength loss caused by increasing the water content to ensure fluidity, which is equivalent to adding weight to the strength side of the fluidity-strength balance, thereby gaining more operating space for the fluidity side.
[0091] III. Enhanced strength throughout all ages This invention achieves full-time strength growth from early to late stages by using a ternary stepped strength system of cement (early stage), slag (mid stage), and fly ash (late stage), superimposed with the synergistic enhancement effect of magnesium slag and oil shale slag.
[0092] In the early stages (0-3 days), cement hydration is the main source of strength. The alkaline environment formed by the hydration of magnesium slag accelerates the cement hydration reaction and promotes the early formation of CSH gel. The porous structure of residual carbon in oil shale slag absorbs free water in the early stage of mixing through capillary adsorption, reducing the effective water-cement ratio in the early stage. At the same time, its slow-release effect provides moisture guarantee for the continuous hydration of cement, further improving the early strength.
[0093] During the intermediate stage (3–14 days), the intensity of the pozzolanic reaction in the slag continuously increases. The magnesia slag continuously provides an alkaline environment, stimulating the dissolution and reaction of active SiO2 and Al2O3 in the slag; the slow-release water supply effect of residual carbon from the oil shale slag ensures sufficient water participation in the intermediate hydration reaction, preventing hydration interruption due to insufficient moisture. The continuous alkalinity supply from the magnesia slag and the slow-release water supply from the oil shale slag work synergistically to allow the pozzolanic reaction in the slag to proceed fully, thus enhancing the intensity increase during the intermediate stage.
[0094] In the later stages (14–28 days and above), the pozzolanic reaction of fly ash continues to contribute to the strength, and the synergistic effect of magnesia slag and oil shale slag is further demonstrated: the micro-expansion effect of f-MgO in magnesia slag compensates for the solidification shrinkage of the slurry, increasing its density; the carbonization reaction of β-C2S utilizes the local carbon source provided by the residual carbon in the oil shale slag to generate CaCO3, further increasing the strength without consuming water; the Mg dissolved from the magnesia slag... 2+ Si dissolved from oil shale slag 4+ / Al 3+ The MSH gel generated in the reaction forms a calcium-magnesium binary composite gel network with the CSH gel in the system, making the microstructure more compact and stable.
[0095] Thus, magnesium slag and oil shale slag both made differentiated contributions to the ternary system throughout the entire age period, forming a complete chain of early acceleration, mid-term continuation, and late-term enhancement, achieving the effect of intensity growth throughout the entire time period.
[0096] IV. Green Environmental Protection and Solid Waste Resource Utilization This invention utilizes industrial solid waste (magnesium slag, oil shale slag, fly ash, and slag) as the main raw materials, supplemented with a small amount of cement, to achieve the synergistic resource utilization of various industrial solid wastes. Magnesium slag and oil shale slag are both bulk industrial wastes, readily available and inexpensive. The widespread application of this invention can effectively dispose of the aforementioned solid wastes, reduce environmental pollution, and significantly lower the cost of delamination grouting materials, aligning with the requirements of green mine construction. Furthermore, both magnesium slag and oil shale slag contain underutilized active components (f-MgO and β-C2S in magnesium slag, and residual carbon, active SiO2, and Al2O3 in oil shale slag). This invention, through specific proportions of compounding, creates multiple synergistic effects among these active components, further improving the resource utilization efficiency of solid waste.
Claims
1. A fly ash-based composite grout for sealing and plugging leaks in coal mine delamination, characterized in that: It consists of the following components in parts by mass: 40-60 parts fly ash; 15-25 parts of slag powder; 8-15 parts cement; Magnesium slag, 10–22.5 parts; 5-15 parts of oil shale residue; Water, with a water-to-solid ratio of 0.8 to 1.2; The mass ratio of magnesium slag to oil shale slag is 1.5:1 to 3:1; Magnesium slag is an industrial waste residue produced by the Pidgeon process for magnesium smelting, which is ground to a specific surface area ≥350m². 2 / kg, which contains f-MgO; oil shale slag is a solid waste residue after dry distillation or combustion of oil shale, which has a porous structure and contains residual carbon, and is ground to a particle size ≤75μm; Oil shale slag has a specific surface area ≥ 400 m² 2 / kg, the pore size distribution of the porous structure is 0.1~10μm.
2. The fly ash-based composite grout for sealing and plugging leaks in coal mine delamination as described in claim 1, characterized in that: The mass ratio of magnesium slag to oil shale slag is 2:
1.
3. The fly ash-based composite grout for sealing and plugging leaks in coal mine delamination as described in claim 1, characterized in that: The fly ash is Class III or higher power plant fly ash, and the slag powder is granulated blast furnace slag powder with a specific surface area ≥ 400 m². 2 / kg, the cement is P.O42.5 ordinary Portland cement.
4. The fly ash-based composite grout for sealing and plugging leaks in coal mine delamination as described in claim 1, characterized in that: The f-MgO content in magnesium slag is 5% to 15%.
5. The fly ash-based composite grout for coal mine delamination grouting and sealing according to claim 1, characterized in that: The β-C2S content in magnesium slag is not less than 40%.
6. The fly ash-based composite grout for sealing and plugging leaks in coal mine delamination as described in claim 1, characterized in that: The fixed carbon content in oil shale residue is 5% to 20%.
7. A method for preparing a fly ash-based composite grout for coal mine delamination grouting and sealing as described in any one of claims 1 to 6, characterized in that: Includes the following steps: Step 1: Grind the magnesium slag powder to a specific surface area ≥ 350 m². 2 / kg; Grind oil shale residue to a particle size ≤75μm; Step 2: Weigh out 40-60 parts of fly ash, 15-25 parts of slag powder, 8-15 parts of cement, 10-22.5 parts of magnesium slag, and 5-15 parts of oil shale slag according to the mass ratio, and put them into a dry powder mixer and stir for 8-15 minutes to obtain a uniform composite dry powder. Step 3: Add the composite dry powder obtained in Step 2 into the pulping machine, add water at a water-to-solid ratio of 0.8 to 1.2, stir for 5 to 10 minutes until the slurry is uniform and free of agglomerates, and the fly ash-based composite slurry is obtained.
8. The application of a fly ash-based composite grout for coal mine delamination grouting and sealing as described in any one of claims 1 to 6 in the filling of coal mine overburden delamination grouting and sealing.
Citation Information
Patent Citations
Fly ash-based grouting filling material
CN101955341A
Method for preparing paste filling material by using oil shale waste residue
CN102108020A